Saccharomyces Cerevisiae Lysate as an Antimycotoxin Feed Additive for Broilers Previously Contaminated by Deoxynivalenol and Fumonisin: Impact on Animal Health and Performance - C Prigol; GM Galli; JV Strapazzon; MS Marchiori; PV Oliveira; RE Mendes; F Matté; FL Gazoni; EM Gloria; LM Stefani; AS Da Silva; MM Boiago (Brazilian Journal of Poultry Science, 2025)
ABSTRACT We evaluated whether the addition of a commercial product made of Saccharomyces cerevisiae lysate (Detoxa Plus®) would be able to minimize the negative effects on performance and health of broilers fed diets contaminated with Deoxynivalenol (DON) and Fumonisin (FB1). A total of 450 male broiler chickens were randomly divided as follows: NC - Negative control diet (without mycotoxin); PC - positive control (diet contaminated with 3 ppm of DON and 30 ppm of FB1); PC+D500 (positive control diet+Detoxa Plus® 500 mg/kg); PC+D750 (positive control diet + Detoxa Plus® 750 mg/kg); PC+D1000 (positive control diet + Detoxa Plus® 1000 mg/kg); NC+D1000 (negative control diet + Detoxa Plus® 1000 mg/kg). Birds fed contaminated diets had lower weight gain (WG) when compared to NC and NC+D1000 at 21 days; however, at 35 and 42 days only birds from the group NC+D1000 showed higher WG. The best feed conversion (FC) was observed in the groups NC and NC+D1000, but birds from the PC+D1000 group showed a similar FC to them. There was an increase in Reactive Oxygen Species and Thiobarbituric Acid Reactive Substances in the liver of PC birds when compared to the other groups. Birds in the NC+D1000 and PC+D1000 groups had the largest intestinal villus size when compared to the other treatments. It is concluded that the consumption of mycotoxins impaired the performance and increased the oxidative stress of the birds. However, the addition of 1000 mg/kg of Detoxa Plus® minimized these negative effects, while also providing larger villus length.